Donor–acceptor–acceptor-type near-infrared fluorophores that contain dithienophosphole oxide and boryl groups: effect of the boryl group on the nonradiative decay. Issue 18 (7th April 2021) - Sugihara, Yoshiaki; Inai, Naoto; Taki, Masayasu; Baumgartner, Thomas; Kawakami, Ryosuke; Saitou, Takashi; Imamura, Takeshi; Yanai, Takeshi; Yamaguchi, Shigehiro
Abstract : Combination of electron-accepting diarylboryl terminal groups and dithienophosphole oxide spacers with electron-donating triarylamine moieties produces donor–acceptor–acceptor type π-systems, which exhibit emissions in the near-infrared region. Abstract : The use of donor–π–acceptor (D–π–A) skeletons is an effective strategy for the design of fluorophores with red-shifted emission. In particular, the use of amino and boryl moieties as the electron-donating and -accepting groups, respectively, can produce dyes that exhibit high fluorescence and solvatochromism. Herein, we introduce a dithienophosphole P -oxide scaffold as an acceptor–spacer to produce a boryl- and amino-substituted donor–acceptor–acceptor (D–A–A) π-system. The thus obtained fluorophores exhibit emission in the near-infrared (NIR) region, while maintaining high fluorescence quantum yields even in polar solvents ( e.g. λ em = 704 nm and Φ F = 0.69 in CH3 CN). A comparison of these compounds with their formyl- or cyano-substituted counterparts demonstrated the importance of the boryl group for generating intense emission. The differences among these electron-accepting substituents were examined in detail using theoretical calculations, which revealed the crucial role of the boryl group in lowering the nonradiative decay rate constant by decreasing the non-adiabatic coupling in the internal conversion process. The D–A–A framework was further fine-tuned to improve the photostability. One of these D–A–A dyes was successfully used in bioimaging to visualize the blood vessels of Japanese medaka larvae and mouse brain.